2001
DOI: 10.1212/wnl.57.8.1515
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of N-acetylcysteine for patients with probable Alzheimer’s disease

Abstract: The antioxidant N-acetylcysteine (NAC) or placebo was administered in a double-blind fashion to patients who met National Institute of Neurological and Communicative Disorders and Stroke-Alzheimer's Disease and Related Disorders Association criteria for probable AD. Testing for efficacy occurred after 3 and 6 months of treatment. Comparison of interval change favored NAC treatment on nearly every outcome measure, although significant differences were obtained only for a subset of cognitive tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
130
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(132 citation statements)
references
References 10 publications
2
130
0
Order By: Relevance
“…Cocco et al [13] reported that old rats treated with NAC showed a slight brain-specific improvement of mitochondrial energy production efficiency, mostly with NAD-dependent substrates, together with a decrease in carbonyl protein content and an increase in the amount of protein thiols of brain cytosolic fraction when compared with untreated animals. Adair et al [1] performed a clinical trial where NAC or placebo was administered in a double-blind fashion to patients with probable AD. They observed that NAC has a positive effect on nearly every outcome measure, although significant differences were obtained only for a subset of cognitive tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Cocco et al [13] reported that old rats treated with NAC showed a slight brain-specific improvement of mitochondrial energy production efficiency, mostly with NAD-dependent substrates, together with a decrease in carbonyl protein content and an increase in the amount of protein thiols of brain cytosolic fraction when compared with untreated animals. Adair et al [1] performed a clinical trial where NAC or placebo was administered in a double-blind fashion to patients with probable AD. They observed that NAC has a positive effect on nearly every outcome measure, although significant differences were obtained only for a subset of cognitive tasks.…”
Section: Discussionmentioning
confidence: 99%
“…NAC is also beneficial in a mouse model of ALS (Andreassen et al 2000). In a 6-month controlled clinical trial of NAC supplementation in Alzheimer's patients, there was a trend for measures of cognitive function to decline less rapidly on all tests employed, albeit significant differences were seen for only a subset of the cognitive tasks (Adair et al 2001).…”
Section: Supplemental Nac In Aging Humans and Rodents Provides Versatmentioning
confidence: 99%
“…N-acetylcysteine (NAC) has some antioxidant properties, and a brief double-blind, placebocontrolled, randomized trial of NAC was undertaken in 43 probable AD patients [158]. Participants received placebo or 50 mg/kg/day of NAC in three diluted doses.…”
Section: Clinical Trials Of Antioxidantsmentioning
confidence: 99%